Physiological and Molecular Mechanism of Nitric Oxide (NO) Involved in Bermudagrass Response to Cold Stress - Fan, Jibiao (PLoS One, 2015)
Bermudagrass is widely utilized in parks, lawns, and golf courses. However, cold is a key factor limiting resource use in bermudagrass. Therefore, it is meaningful to study the mechanism of bermudagrass response to cold. Nitric oxide (NO) is a crucial signal molecule with multiple biological functions. Thus, the objective of this study was to investigate whether NO play roles in bermudagrass response to cold. Sodium nitroprusside (SNP) was used as NO donor, while 2-phenyl-4,4,5,5-tetramentylimidazoline-l-oxyl-3-xide (PTIO) plus N(G)-nitro-L-arginine methyl ester (L-NAME) were applied as NO inhibitor. Wild bermudagrass was subjected to 4 °C in a growth chamber under different treatments (Control, SNP, PTIO + L-NAME). The results indicated lower levels of malondialdehyde (MDA) content and electrolyte leakage (EL), higher value for chlorophyll content, superoxide dismutase (SOD) and peroxidase (POD) activities after SNP treatment than that of PTIO plus L-NAME treatments under cold stress. Analysis of Chlorophyll (Chl) a fluorescence transient displayed that the OJIP transient curve was higher after treatment with SNP than that of treated with PTIO plus L-NAME under cold stress. The values of photosynthetic fluorescence parameters were higher after treatment with SNP than that of treated with PTIO plus L-NAME under cold stress. Expression of cold-responsive genes was altered under cold stress after treated with SNP or PTIO plus L-NAME. In summary, our findings indicated that, as an important strategy to protect bermudagrass against cold stress, NO could maintain the stability of cell membrane, up-regulate the antioxidant enzymes activities, recover process of photosystem II (PSII) and induce the expression of cold-responsive genes.